2011
DOI: 10.1159/000324858
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Vestibular Evoked Myogenic Potentials: Frequency Tuning to Air-Conducted Acoustic Stimuli in Healthy Subjects and Ménière’s Disease

Abstract: Ocular vestibular evoked myogenic potentials (oVEMP) in response to 250-, 500- and 1000-Hz air-conducted short tone bursts were studied in 22 healthy subjects and 37 Ménière’s disease patients. The goal of this study was to investigate normal tuning characteristics of the oVEMP and the possible oVEMP changes with respect to frequency dependence in Ménière’s disease. In unilateral Ménière’s disease patients, a distinction was made between affected ears and unaffected ears. It was found that in normal subjects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 52 publications
5
34
0
3
Order By: Relevance
“…Rauch et al [2004] were the first to demonstrate that VEMP tuning could be altered by pathology that affects the mechanics of the inner ear. Instead of demonstrating optimal responses at 500 Hz, as is the trend for most control subjects, patients with Ménière's disease exhibited higher amplitudes and lower thresholds at a frequency of 1 kHz Lin et al, 2006;Murofushi et al, 2009;Kim-Lee et al, 2009;Winters et al, 2011]. This upward shift in resonance was attributed to the presence of endolymphatic hydrops in the otolith organs, causing an increase in stiffness .…”
Section: Introductionmentioning
confidence: 89%
“…Rauch et al [2004] were the first to demonstrate that VEMP tuning could be altered by pathology that affects the mechanics of the inner ear. Instead of demonstrating optimal responses at 500 Hz, as is the trend for most control subjects, patients with Ménière's disease exhibited higher amplitudes and lower thresholds at a frequency of 1 kHz Lin et al, 2006;Murofushi et al, 2009;Kim-Lee et al, 2009;Winters et al, 2011]. This upward shift in resonance was attributed to the presence of endolymphatic hydrops in the otolith organs, causing an increase in stiffness .…”
Section: Introductionmentioning
confidence: 89%
“…Also, VEMP thresholds at multiple frequencies yield, at least in Menière's disease patients, a more sensitive measure with less intersubject variability (in normals), further increasing the clinical utility of the cVEMP [van Tilburg et al, submitted paper]. Threshold measurements in oVEMPs have also been shown to differ between healthy and pathological subjects [161]. Furthermore, using only a present/absent criterion, the degree of damage to the otoliths is not measurable.…”
Section: Challenges In Establishing a Diagnosis Of Bvhmentioning
confidence: 99%
“…Patients with MD have been shown to have lower VEMP than normal controls [Winters et al, 2012], though it has also been demonstrated that VEMP can be normal or even augmented, particularly in the earlier stages of the disease [Wen et al, 2012;Young et al, 2003]. Although several studies showed subjects with MD to have significant abnormalities in cVEMP and oVEMP, there is wide variation in the results [Taylor et al, 2011].…”
mentioning
confidence: 99%